The Role of Immunocytochemical Markers to Differentiate Primary from Secondary Neoplastic Hepatic Masses: A Diagnostic Challenge on Cytology - Jenna B BHATTACHARYA; Shyam Lata JAIN; Subbarayan DEVI (Federation of Turkish Pathology Societies, 2021)
Objective: It is challenging and difficult to differentiate primary from metastatic hepatic masses solely on cytology. The present study aimed to correlate cytomorphological spectrum of hepatic masses with immunocytochemical markers to differentiate primary from metastases in liver. Material and Method: The present study comprised of 30 clinico-radiologically suspicious cases of neoplastic hepatic masses. Ultrasound-guided fine needle aspiration smears and cell blocks were prepared as per standard technique; two of the smears were air-dried and Giemsa stained to study cytomorphological features. A panel of markers (HepPar-1, CD 10, CK7, CK19, CD34, and MOC-31) were studied both in smears and cell blocks. Results: Cytomorphological features on smears were evaluated and correlated with immunocytochemistry in all cases; the final diagnosis was: Hepatocellular carcinoma (n=7), cholangiocarcinoma (n=2), hepatoblastoma (n=1) and metastatic carcinoma (n=20). HepPar-1, CD10 and CD34 demonstrated 86%, 72%, 86% sensitivity and 100% specificity respectively for hepatocellular carcinoma; CK7&CK19 showed 100% sensitivity for cholangiocarcinoma, MOC 31 showed 90% sensitivity and 100% specificity for metastatic carcinoma.Conclusion: The present study recommends a panel of minimum three markers (HepPar-1, CD10, and MOC-31) which were helpful to differentiate hepatocellular carcinoma from metastatic carcinoma that was a major diagnostic challenge solely on cytomorphology. Correlating cytomorphology with these three markers, 100% of the cases could be diagnosed as primary malignancy and distinguished accurately from metastatic carcinoma.